Synthesis, crystal structure and properties of catena-poly[[bis(4-methylpyridine-κN)cobalt(II)]-di-μ-thiocyanato-κ2N:S;κ2S:N], which shows a rare coordination geometry - Christian Näther; Jan Boeckmann (Acta Crystallographica Section E: Crystallographic Communications)
Reaction of Co(NCS)2 with 4-methylpyridine in water leads to the formation of single crystals of the title compound, [Co(NCS)2(C6H7N)2]n. The asymmetric unit consists of two crystallographically independent thiocyanate anions and two crystallographically independent 4-methylpyridine coligands in general positions, as well as of two different CoII cations, of which one is located on a twofold rotational axis, whereas the second occupies a center of inversion. The methyl H atoms in both 4-methylpyridine ligands are disordered and were refined using a split model. Both CoII cations are octahedrally coordinated by two N- and two S-bonded thiocyanate anions and two 4-methylpyridine coligands and are linked by pairs of 1,3-bridging anionic ligands into chains. Within these chains the cations show an alternating all-trans and cis–cis–trans configuration, which leads to the formation of corrugated chains. Powder X-ray diffraction proves that a pure crystalline phase has been obtained and the values of the CN stretching vibrations of the anionic ligands observed in the IR and the Raman spectra are in agreement with the presence of bridging anionic ligands.